STUDI KASUS UMPAN BALIK GURU PADA PERSEPSI SISWA KELAS IV SD DALAM IMPLEMENTASI KURIKULUM MERDEKA - Afrilia, Nurisa; Mahya Fanny, Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the perceptions of fourth-grade elementary school students regarding teacher feedback in the implementation of the Independent Curriculum, the obstacles experienced by teachers in providing feedback, and the solutions implemented by teachers to overcome these obstacles. This study used a qualitative approach with a case study type. Data were collected through student questionnaires, in depth interwiews and documentation involving fourth-grade teachers and fellow teachers. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data collection, data reduction, data presentation and conclusions. The resulst showed that student perceived the feedback provided by teachers to increase their metacognitive awareness, where student were able to identify arrors and understand the corrective steps that must be taken, as well as increasing intrinsic motivation. Although some of them still felt hesistant to ask and receive feedback directly. Barriers experienced by teachers include differences in characteristics, student comprehension,time constraints and student psychological factors. Solution implemented by teachers included verbal feedback, a personalized approach, peer tutoring, learning differention and strengthening appreciation for the process of student effort. This study concluded that teacher feedback needs to be provided adaptively according to student characteristics. It is recommended that teachers continue to improve flexible feedback strategies and create a supportive learning environment.